Evaluation of the Conceptual Model on Shrubbiness-Desertification on Arid Rangelands - Torres, Y A; Busso, C A; Ithurrart, L S; Ambrosino, M L (Annals of Arid Zone, 2019)
Advancement of shrubbiness (increase in plant cover and density of woodyspecies) on different environments world-wide has generated an increasing interest inthe scientific community, particularly because of its association with the desertificationprocess which is increasing, also at a world-wide level. There are two opposingpositions, both of them validated by scientific evidences. The greatly accepted positionrecognizes shrubbiness as one of the mechanisms conducive to desertification in naturalenvironments, cataloguing it as a negative process. A different view, based on recentstudies, suggests that shrubbiness should be considered as a positive process because itmay drive a reversal of desertification, depending on the environment and the speciesof shrub studied at a site. This review presented within this framework discusses theexisting relationship between shrubbiness and desertification and proposes an approachthat should be considered in future research.Key words: Shrubbiness, desertification, arid rangelands, arbuscular mycorrhiza, soilbiological crusts.